Clinical significance of cervical MRI in brachial plexus birth injury - Grahn, Petra; Pöyhiä, Tiina; Sommarhem, Antti; Nietosvaara, Yrjänä (Acta Orthopaedica, 2019)
Background and purpose — Patient selection for nerve surgery in brachial plexus birth injury (BPBI) is difficult. Decision to operate is mostly based on clinical findings. We assessed whether MRI improves patient selection. Patients and methods — 157 BPBI patients were enrolled for a prospective study during 2007–2015. BPBI was classified at birth as global plexus injury (GP) or upper plexus injury (UP). The global plexus injury was subdivided into flail upper extremity (FUE) and complete plexus involvement (CP). Patients were seen at set intervals. MRI was scheduled for patients that had either GP at 1 month of age or UP with no antigravity biceps function by 3 months of age. Type (total or partial avulsion, thinned root), number and location of root injuries and pseudomeningoceles (PMC) were registered. Position of humeral head (normal, subluxated, dislocated) and glenoid shape (normal, posteriorly rounded, pseudoglenoid) were recorded. Outcome was assessed at median 4.5 years (1.6–8.6) of age. Results — Cervical MRI was performed on 34/157 patients at median 3.9 months (0.3–14). Total root avulsions (n = 1–3) were detected on MRI in 12 patients (8 FUE, 4 CP). Reconstructive surgery was performed on 10/12 with total avulsions on MRI, and on all 10 with FUE at birth. Sensitivity and specificity of MRI in detecting total root avulsions was 0.88 and 1 respectively. Posterior shoulder subluxation/dislocation was seen in 15/34 patients (3.2–7.7 months of age). Interpretation — Root avulsion(s) on MRI and flail upper extremity at birth are both good indicators for nerve surgery in brachial plexus birth injury. Shoulder pathology develops very early in permanent BPBI.